Constructive anarchy : building infrastructures of resistance - Shantz, Jeff. (Farnham, Surrey, England ; Burlington, VT : Ashgate Pub. Co., 2010)
Constructive Anarchy draws on over a decade of direct study within a variety of anarchist projects to provide the most wide-ranging and detailed analysis of current anarchist endeavours to date. The book offers compelling discussions of anarchism and union organizing, anti-poverty work and immigrant and refugee defence, and is a groundbreaking achievement from one of the rising scholars of contemporary anarchism.
Foreword -- Introduction: Constructive Anarchy -- 1 Organizing Anarchy: Debates and Directions -- 2 "Seize the Switches": Media and Anarchy -- 3 Whatever it Takes: The Ontario Coalition Against Poverty -- 4 Anarchy at Work: Developing Workers' Autonomy -- 5 Building Bridges: Anarchism, Borders and Resistance -- 6 Anarchy Goes to School: The Anarchist Free Skool -- 7 Re-Thinking Revolution: A Constructive Anarchist Approach -- Conclusion:"Quiet Revolutions" -- References -- Index.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Anarchists -- Political activity; Anarchists -- Political activity -- North America; Anarchism -- North America; Anarchistes -- Activité politique; Anarchistes -- Activité politique -- Amérique du Nord; Anarchisme -- Amérique du Nord; POLITICAL SCIENCE -- Political Ideologies -- Anarchism; Anarchism; North America